2015
DOI: 10.1093/scan/nsv119
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of trait self-esteem revealed by the amplitude of low-frequency fluctuations and resting state functional connectivity

Abstract: Self-esteem is an affective, self-evaluation of oneself and has a significant effect on mental and behavioral health. Although research has focused on the neural substrates of self-esteem, little is known about the spontaneous brain activity that is associated with trait self-esteem (TSE) during the resting state. In this study, we used the resting-state functional magnetic resonance imaging (fMRI) signal of the amplitude of low-frequency fluctuations (ALFFs) and resting state functional connectivity (RSFC) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 96 publications
1
18
0
1
Order By: Relevance
“…As another popular measure for low‐frequency fluctuations correlations, resting‐state functional connectivity (RSFC) reflects the synchronization among different brain regions (Fox & Raichle, ). Increasing evidence has suggested that RSFC is a good neural marker of personality traits (e.g., Adelstein et al, ; Pan et al, ; Sampaio et al, ; Takeuchi et al, ; Wang et al, ). In summary, fALFF and RSFC are suitable for examining the neural bases of trait optimism.…”
Section: Introductionmentioning
confidence: 99%
“…As another popular measure for low‐frequency fluctuations correlations, resting‐state functional connectivity (RSFC) reflects the synchronization among different brain regions (Fox & Raichle, ). Increasing evidence has suggested that RSFC is a good neural marker of personality traits (e.g., Adelstein et al, ; Pan et al, ; Sampaio et al, ; Takeuchi et al, ; Wang et al, ). In summary, fALFF and RSFC are suitable for examining the neural bases of trait optimism.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the threshold for significant clusters was set as follows: 10,000 iterations, p < 0.05 at the cluster level combined with a p < 0.005 at the voxel level, at least 50 voxels (1350 mm 3 ). AlphaSim is a popular program used in previous studies to analyze RS-MRI data 29 31 , 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Resting-state functional connectivity (RSFC) is another popular and reliable indicator reflecting synchronization among multiple brain regions 22 , 24 , 32 . Evidence from many previous investigations has indicated that RSFC is an excellent predictor of personality traits 33 – 35 . Thus, fALFF and RSFC are useful tools for uncovering the neural substrates of DD.…”
Section: Introductionmentioning
confidence: 98%
“…低频振幅(amplitude of spontaneous low-frequency fluctuation, ALFF; 0.01~0.08 Hz)是大脑自发神经活动 强度的神经指标, 主要反映了特定脑区静息状态下的 局部自发活动属性 [29] . 在认知功能上, ALFF被认为可 以反映在人格特质和认知控制上的个体差异 [25,30,31] .…”
Section: 近年来研究者开始较多关注大脑自发神经活动在认知 加工中的作用unclassified